(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Dozens of chemical fertilizer is produced in factors to maintain and reclaim soil fertility, but the reliance on artificial fertilizer alone is not advisable due to environmental pollution. . Thus, indigenous plant species can maintain soil fertility without any extra cost. The aim of this study was to examine the effect of indigenous tree species on soil physical properties. Three dominant indigenous trees species (Croton macrostachuys, Cordia Africana and Albizia gummifera) were considered. Soil samples were taken from different sampling points under crown of these tree species (mid of crown and edge of crown). One sampling point is included by far 30m from the selected tree as a control group. Soil sample was taken by using core sampler. Soil physical properties such as texture, structure, porosity, bulk density and moisture content were analyzed. Bulk density was determined as 0.73g/cm3, 0.75g/cm3 and 0.8g/cm3 for Albizzia gummifera, Croton macrostachuys and Cordia Africana respectively. Bulk density was very small under crown of all trees as influenced by the amount of organic matter falling from trees leaf. The texture under crown of all tree species (silty loam, loam and loamy sand) is quite better for agriculture purpose than control point. Soil color under crown is in the range of brown to black color, which indicates high fertility level. Soil porosity was very high under the crown of all tree species as compared to the control site. It is determined as 72.5%, 71.6%, and 69.7% for Albizzia gummifera, Croton macrostachuys and Cordia Africana respectively. Soil consistence, porosity and moisture content were better under crown of the trees than control group. Soil properties under the crown of indigenous tree species were better than bare land soils. Therefore, indigenous trees are promising option to maintain soil fertility level and land owners ought to be aware of this miracle.